2010
DOI: 10.1021/jp106063c
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Raman and Luminescence Study on the Phase Transition of GdVO4:Eu3+ Microcrystals

Abstract: The Raman and luminescence spectra of GdVO 4 :Eu 3+ microcrystals have been measured in the pressure range from ambient pressure to 16.4 GPa at room temperature by using a diamond anvil cell. The discontinuities on Raman mode and luminescence intensity and the appearance of new Raman bands and luminescence peaks have provided strong evidence for a phase transition at 7.4 GPa from zircon-type to scheelite-type structure, and the zircon-type and scheelite-type phases coexist over a pressure range of 7.4-16.4 GPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 18 publications
4
41
2
Order By: Relevance
“…The different red shift for the 5 D 0 → 7 F (0, 1,2) transitions of the Eu 3+ ions was observed in other nanomaterials in size about 10-60 nm (20,21). Contrary to the nanoparticle in microcrystals in size about 200-500 nm (12), the sharp emission peaks due to the 5 D 0 → 7 F 1 transition are located at 593.7 and 594.2 nm. The two strongest lines from the 5 D 0 → 7 F 2 transition are at 615 and 619 nm (12).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The different red shift for the 5 D 0 → 7 F (0, 1,2) transitions of the Eu 3+ ions was observed in other nanomaterials in size about 10-60 nm (20,21). Contrary to the nanoparticle in microcrystals in size about 200-500 nm (12), the sharp emission peaks due to the 5 D 0 → 7 F 1 transition are located at 593.7 and 594.2 nm. The two strongest lines from the 5 D 0 → 7 F 2 transition are at 615 and 619 nm (12).…”
Section: Resultsmentioning
confidence: 75%
“…Peaks at 615 and 619 nm ( 5 D 0 → 7 F 2 transition) are electric dipole transition, while 593.7 and 594.2 nm ( 5 D 0 → 7 F 1 transition) are magnetic dipole transitions (12,13). The 5 D 0 → 7 F 1 , 5 D 0 → 7 F 3 , and 5 D 0 → 7 F 4 transition lines are henceforth neglected because they are disturbed by the sensor (SrFCl:Sm 2+ ) fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…7,23−27 Unlike scheelite-type ABO 4 compounds in which the transition pressures would increase with the ratio r BO 4 /r A , where r BO 4 and r A present the radii of BO 4 units and A-site cation, 28 Errandonea et al found the zircon-to-scheelite phase transition pressure (P T ) for a specific family of zircon-type ABO 4 compounds is quite close and nearly independent of the A cation size. 11 For instance, the P T for orthovanadates is always around 7−8 GPa, 11,14,20 the P T for the silicates and phosphates is around 20 GPa, 7,23,27 and that for the chromates is below 6 GPa. 29 4 and PO 4 polyhedra probably make the zircon structure more stable, while cooperative interactions between the 3d electrons of the transition metals in vanadates and chromates could make the zircon structure less stable upon compression.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The previous investigation results indicated that the luminescence properties of the phosphors depended on their sizes and morphologies [16,17], therefore, the controllable preparation of the size, microstructure and morphology of the phosphor have been paid much attention. Recently, GdVO 4 with different morphologies such as nanowires, nanorods, nanofibers and nanoparticles have been reported [5,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%